Preaching (as) atonement - Pleizier, Theo (Stellenbosch Theological Journal, 2019)
Atonement is a central doctrine in Christian theology. Even though preaching is not about doctrines, doctrine does operate in and through preaching. In this essay the relationship between atonement and preaching is explored. Based upon a contemporary theological analysis of atonement by Eleonore Stump, two homiletic aspects of the relationship between atonement and preaching are presented: atonement in preaching and atonement through preaching. As a study in homiletical theology, the essay challenges common binaries in homiletics, such as between proclamation and poetics, and presents a way of dealing with fundamental Christian doctrines in the theory of preaching.